2014
DOI: 10.1016/j.jcorpfin.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Executive board composition and bank risk taking

Abstract: Little is known about how socioeconomic characteristics of executive teams affect corporate governance in banking. Exploiting a unique dataset, we show how age, gender, and education composition of executive teams affect risk taking of financial institutions. First, we establish that age, gender, and education jointly affect the variability of bank performance. Second, we use difference-in-difference estimations that focus exclusively on mandatory executive retirements and find that younger executive teams inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
175
6
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 511 publications
(201 citation statements)
references
References 109 publications
(119 reference statements)
16
175
6
4
Order By: Relevance
“…The findings are consistent with the studies that found a negative relation between gender diversity and risk-taking predicting that board females are risk averse [11,47]. Board members with a PhD degree has positive insignificant relation with the three measures of risks which is a contrast to the finding of [9], who find that better educated board members decrease portfolio risk, and with [20], who found higher education increase the bank risk-taking.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The findings are consistent with the studies that found a negative relation between gender diversity and risk-taking predicting that board females are risk averse [11,47]. Board members with a PhD degree has positive insignificant relation with the three measures of risks which is a contrast to the finding of [9], who find that better educated board members decrease portfolio risk, and with [20], who found higher education increase the bank risk-taking.…”
Section: Resultssupporting
confidence: 89%
“…", the study found that Board member with a PhD has a positive insignificant relation with the three measures of risks, accordingly, the results don't support hypothesis 5. However, This is in contrast with the finding of [9], who find that better educated members in the board of directors decreases portfolio risk, suggesting that they apply better risk management techniques, and with [20], who show that higher education increase the bank risk taking. It seems that it is not the qualification only that affect the bank risk taking but also the way the members leverage their knowledge and skills with their educational qualifications in enhancing the bank efficiency.…”
Section: Results Of Correlation and Regression Analysiscontrasting
confidence: 79%
See 2 more Smart Citations
“…First, to the best of our knowledge, this is one of the earliest studies to systematically investigate the issue of gender diversity on bank performance for a leading emerging economy. Most studies of this genre are either cross-country in nature (Andres and Vallelado, 2008;Garcia-Meca et al, 2015) or, even if they are within-country studies, are focused primarily on developed countries (de Cabo et al, 2012;Berger et al, 2013;Del Prete and Stefani, 2013;Pathan and Faff, 2013) or economies such as China (Liang et al, 2013) and Korea (Choi and Hasan, 2005). Little, if any, systematic empirical evidence is available for India, and this is one of the major concerns of the paper.…”
Section: Introductionmentioning
confidence: 99%